Studi Kualitatif Gaya Komunikasi Manajerial Terhadap Pembentukan Motivasi Dan Sikap Karyawan - Bambang Mudjiyanto; Launa; Hayu Lusianawati; Faisyal (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
This study intends to analyze the findings of previous research results related to the impact of managerial communication styles on the formation of employee motivation and attitudes which will be examined through the concept of interpersonal communication, the concept of organizational communication, social exchange theory and organizational support theory. This type of research is qualitative with a literature review approach as an analytical method. The research results show that communication styles and managerial leadership styles have a positive impact on the formation of employee motivation and attitudes. The personality of company leaders is also an important variable in growing employee confidence. The level of communication satisfaction is another variable that can strengthen the emotional bond between employees and company managers. The leader's personality factor, assertive communication style and the visionary-organic leadership paradigm are proven not only to influence the formation of the technical aspects of supervision, but also to the psychological aspects of employees, namely the high support and commitment of employees to the company.